Activities of the Minister of Internal Affairs of the Ukrainian SSR Pavlo Yakovlevych Meshyk (1953) - V. A. Grechenko (Law and Safety)
The article examines the insufficiently studied in historical and legal science issue of the activities of such a controversial political figure of the first post-Stalin months of 1953 as Pavlo Yakovlevych Meshyk. It is emphasised that he, having a university degree (which was rare for NKVD personnel in those years) and significant organisational skills, made a successful career in the central apparatus of the People’s Commissariat in the late 1930s. This was also due to the patronage of P. Meshyk by L. Beria. P. Meshyk was directly involved in Stalin’s repressions. In 1941, at the age of 30, he first became People’s Commissar for State Security of the Ukrainian SSR. In 1943, he was promoted to the rank of Lieutenant General. From 1945 until March 1953, he worked on the implementation of the Soviet nuclear project. He was awarded the Order of Lenin (1949) for his active participation in the implementation of the nuclear programme, and later even received the Stalin Prize in Science and Technology (1951). In March 1953, he was appointed Minister of Internal Affairs of the Republic, where he pursued a policy of strengthening the rule of law in the activities of the state security agencies and purging them of the most odious and incompetent employees. At the same time, a policy was implemented to rid the state security agencies of their dependence on the influence of the Communist Party. At the same time, P. Meshyk came into conflict with some party officials, including the then leader of the republic, the first secretary of the Central Committee of the CP(B)U, L. Melnikov. As a result, L. Melnikov was dismissed. P. Meshyk also took some measures to “root” the leadership of the Ministry of Internal Affairs, translated the ministry’s office work into Ukrainian, eased some of the Soviet government’s repressive policies towards the Ukrainian national liberation movement, actually restored the normal operation of Lviv State University, and improved contacts with Western Ukrainian intellectuals. These were positive aspects of the minister’s activities that can be assessed as attempts at reform. However, P. Meshyk stayed in the post of Minister of the Interior for only three months. In June 1953, he was arrested and later convicted on charges of treason and conspiracy to seize power, and in December of the same year, Meshyk was shot dead. He was partially rehabilitated in 2000.